Fatigue experimental characterisation of brazed joints in aluminium microchannel heat exchangers (Fracture and Structural Integrity, 2025)
Brazing is a widely employed joining technique for aluminium components due to its cost-effectiveness and compatibility with complex geometries. However, the structural integrity of brazed joints under cyclic loading remains a scarcely addressed scientific and engineering concern. This study investigates the tensile and fatigue behaviour of aluminium 3xxx-series alloy components employed in microchannel heat exchangers—headers and multi-port extruded tubes—both in the as-received and heat-treated (brazing cycle) conditions. Tensile tests were performed on parent materials using a microtensile equipped with a Digital Image Correlation (DIC) system for accurate strain evaluation during testing. On the other hand, uniaxial fatigue tests were performed on specimens containing a representative brazed joint. Finite element analyses were used to design the fatigue specimen geometry based on stress concentrations observed in simplified heat exchanger models. Fatigue test data were employed to determine fatigue behaviour both in the finite life region of high-cycle fatigue and to characterise the fatigue endurance limit at 107 cycles. Experimental testing unveiled crack initiation consistently occurring at the brazed fillet toe near the tube lateral edge. SEM observations revealed surface-initiated cracking, ratchet marks, sub-surface inclusions and final ductile failure. Results underline the need for fatigue-based design criteria for brazed aluminium structures.
Keywords: Brazed joint; microchannel heat exchanger; fatigue; aluminium alloy